Improving interface design of game-based learning courseware / Nur 'Atiqah Bahirah Raidah Ahmad Zubaidi - Ahmad Zubaidi, Nur 'Atiqah Bahirah Raidah (2011)
Game has traditionally been used in learning, particularly in preschool education. There are many game-based courseware applications available and have been included as part of the children's syllabus to support learning these days. However, most of these game-based learning coursewares have not been tested for learnability. The paper focuses on to find out whether the game-based learning courseware is supporting learnability to preschool children or not. To conduct the study, a method of usability testing that allows preschool children ages 5 to 6 years old to play with the game-based learning courseware was used. From the usability testing, the interface design problems in the game-based learning courseware have been analyzed and improved based on literature reviews of previous researchers and SEM model. After the improvement done, the game-based learning have been tested again and findings gained. The findings show that the game-based learning courseware has the learnability element but yet there were few issues have to be improved. For future study, a few suggestions of effective interface and interaction design for game-based learning courseware have been given based on the findings. Keywords Learnability, interface design, game-based learning courseware.